Investigating the Relationship between Organizational Culture, Compensation, Spiritual Leadership, and Teacher Performance in Private Islamic Elementary Schools - Syahid Syahid; E. Syarifuddin; Agus Gunawan (International Journal of Science Education and Cultural Studies, 2024)
This research aims to analyze the influence of Organizational Culture (OC) on teacher performance (TP), the influence of compensation (C) on TP, and the influence of spiritual leadership (SL) on TP, as well as the combined influence of OC, C, and SL of the on TP. Data analysis was conducted at a significance level of 0.5%. The results are as follows: There is a significant influence of OC on TP, as evidenced by the t-test result showing that t-value 22.458 > t-table 1.966 and Sig 0.000 < 0.05; thus, hypothesis H1 is accepted. There is a significant influence of C on TP, as evidenced by the t-test result showing that t-value 2.420 > t-table 1.966 and sig 0.016 < 0.05; thus, hypothesis H2 is accepted. There is a significant influence of the SL on TP, as evidenced by the t-test result showing that t-value 2.379 > t-table 1.966 and sig 0.18 < 0.05; thus, hypothesis H3 is accepted. Based on the F-test, the calculated F-value is 578.741; because the calculated F-value 578.741 > F-table 2.395, it means that hypothesis H4 is accepted, or in other words, OC, C, and SL collectively influence TP. The coefficient of determination test yields a Coefficient of Determination (R-Square) for TP of 0.819, exceeding the value of 0.67, indicating that the independent variables collectively have a strong influence, accounting for 81.9% of TP. In conclusion, there is a significant combined influence of (X1), (X2), and (X3) on TP. This influence is direct and accounts for 81.9%, while the remaining 18.1% is influenced by other variables not tested in this research. These findings have an impact on TP in private madrasah ibtidaiyah. Therefore, the research findings recommend that the performance of private madrasah ibtidaiyah teachers can be improved through OC, C, and SL.